PREVALENCE OF HIGH CARCINOGENIC RISK HUMAN PAPILLOMAVIRUS IN THE REPUBLIC OF SAKHA (YAKUTIA), ST. PETERSBURG AND THE REPUBLIC OF KARELIA - L. V. Lyalina; M. E. Ignatyeva; O. V. Narvskaya; Yu. N. Filippova; A. A. Vyazovaya; E. V. Kasatkin; E. V. Katkyavichene (Acta Biomedica Scientifica, 2012)
Results of the study in three regions of the Russian Federation have shown widespread of high carcinogenic human papillomavirus among patients of dermatovenerological and gynecological profile. Detection of viral DNA in the material from the cervix and urethra ranged from 25,2 (Karelia) to 42,5 (Sakha Republic (Yakutia) per 100 examined patients. In all areas in 2010-2011 first place was occupied by 16-th virus genotype - from 11,5 (Sakha Republic (Yakutia) to 15,9 (St. Petersburg) per 100 patients. Prevalence of 11 other types differs. In the Sakha Republic (Yakutia) the second rank place was occupied by types 31 and. 51 (8,0 per 100 examined patients), in St. Petersburg - by 56 and 31 types (9,7 and. 7,6 per 100 patients). Age risk group contains patients of the age of 20-29 years. Information on circulating genotypes of the virus is a necessary part of surveillance to validate vaccination against human papillomavirus infection and evaluation of its efficiency.